Analisis Upaya Rumah Sakit dalam Menutupi Kekurangan Biaya Klaim Indonesia Case Base Group (INA-CBGs) Yang Dihitung dengan Metode Activities Base Costing pada Rumah Sakit Swasta Kelas C di Kota Medan Tahun 2017 - Aulia, Destanul; Ayu, Sri Fajar, Universitas Sumatera Utara (Jurnal Ekonomi Kesehatan Indonesia, 2017)
Indonesia has developed the National Social Insurance System with the establishment of the National Health Insurance program and organized by BPJS Kesehatan. One of payment way of health services for the hospital in the era of JKN is Indonesian Case Base Group (INA-CBG’s), that is the payment of claims from BPJS to hospital on a package of services based on the packet of disease diagnosis and procedure.This study aims to analyze efforts by hospitals to cover the cost deficiency of INA CBG’s claims in Privat Hospital in Medan. This research type is descriptive with qualitative and quantitative. Qualitative is done by in-depth interview, and quantitative is done by calculating real cost and cost of INA-CBG’s claim and by Activity Based Cost method. The counting result with ABC system,The results showed that the efforts made by hospitals to cover INA-CBG’s claim cost deficits are utilizing the help of health professionals from students from private hospital schools / academies, length of service delivery, setting out service packages for general patients, and providing patient pickup facilities. Suggested to to the Hospital to evaluate the financial risks the hospital receives from services, practice student performance, and distribute the cost of INA CBG’s claims well in order to improve the quality of health services in accordance with the standards.